2020
DOI: 10.1002/cmdc.202000096
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Anticancer Activity of an Electron‐Deficient Organoruthenium(II) Complex

Abstract: Ruthenium compounds have been shown to be promising alternatives to platinum(II) drugs. However, their clinical success depends on achieving mechanisms of action that overcome Pt‐resistance mechanisms. Electron‐deficient organoruthenium complexes are an understudied class of compounds that exhibit unusual reactivity in solution and might offer novel anticancer mechanisms of action. Here, we evaluate the in vitro and in vivo anticancer properties of the electron‐deficient organoruthenium complex [(p‐cymene)Ru(m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 61 publications
(18 reference statements)
1
15
0
Order By: Relevance
“…The possibility of using compounds 1-4 as a transfer hydrogenation catalyst to reduce NAD + was investigated (Materials and Methods section). Compounds 1-4 reduced NAD + with turnover frequencies (TOF) between 6 and 15 h −1 (Table 1), which is within the range of previously reported compounds [51,53,[74][75][76]. Remarkably, under the conditions here reported (MeOD/D 2 O 1:1 v/v, 310 K, pH* 7.4 ± 0.2), the iridium complex 2 reduced nine molar equivalents of NAD + within the initial 10 min.…”
Section: Catalytic Reactions With Nicotinamide Adenine Dinucleotidesupporting
confidence: 87%
See 2 more Smart Citations
“…The possibility of using compounds 1-4 as a transfer hydrogenation catalyst to reduce NAD + was investigated (Materials and Methods section). Compounds 1-4 reduced NAD + with turnover frequencies (TOF) between 6 and 15 h −1 (Table 1), which is within the range of previously reported compounds [51,53,[74][75][76]. Remarkably, under the conditions here reported (MeOD/D 2 O 1:1 v/v, 310 K, pH* 7.4 ± 0.2), the iridium complex 2 reduced nine molar equivalents of NAD + within the initial 10 min.…”
Section: Catalytic Reactions With Nicotinamide Adenine Dinucleotidesupporting
confidence: 87%
“…In order to determine whether ROS formation is a plausible explanation for the activity of these compounds, A2780 cells were treated at IC 50 concentrations of 1 – 4 in combination with increasing concentrations of N -acetylcysteine (NAC; 0, 2, 5 and 10 mM; Figure 4 ). NAC is a known compound that can act as an ROS scavenger in cells and can be used to counteract the effects of complexes that affect ROS levels [ 76 , 77 ]. Interestingly, the addition of complexes 1 and 2 to NAC-supplemented cells leads to a significant decrease of the cell viability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have shown a promising characterization as an immune-modulating anticancer agent, 145 excellent redox potential, 97 strong topoisomerase inhibitor, 98 while others have shown encouraging results such as antimetastatic activity, tubulin formation inhibition, and high selectivity against cancer cells over normal cells. [146][147][148] Recent investigations cover structurally novel scaffolds including electron-deficient ruthenium complexes 149 and macromolecular ligands such as dendrimers. 150 In this review, we present a brief description of Ru-based anticancer complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Barry and co‐workers demonstrated that electron‐deficient metal complexes can also induce the production of high levels of ROS in cancer cells with the complex [( p ‐cymene)Ru(maleonitriledithiolate)] increasing ROS levels in ovarian A2780 cancer cells and the ROS‐scavenger NAC inhibiting the cytotoxicity of this metal complex (Figure 9). [143] …”
Section: Metal‐based Anticancer Drug Candidates Causing Oxidative Str...mentioning
confidence: 99%